Pengaruh Current Ratio, Net Profit Margin, Debt To Equity Ratio Dan Total Assset Turnover Terhadap Nilai Perusahaan - Idris Idris (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The purpose of this study was to determine the effect of the Current Ratio, Net Profit Margin, Debt to Equity Ratio and Total Asset Turnover on Company Value. This research uses a sample of automotive and component sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022 using the purposive sampling method. The data used are the financial statements of automotive and component sub-sector manufacturing companies listed on the Indonesia Stock Exchange for 2018-2022 and there are 12 companies that meet the criteria. The analysis method used in this study is multiple linear regression analysis using the Statistical Package for Social Science (SPSS) program version 25. The results of testing this hypothesis show that there is a significant influence between Debt to Equity Ratio and Total Asset Turnover on Company Value, while Current Ratio, Net Profit Margin has no effect on Company Value.